Bilateral Visual Loss as Presenting Symptom of Posterior Reversible Encephalopathy Syndrome in a Patient with HIV/Tuberculosis Coinfection: A Case Report - S. Guerriero; L, Ciracì; T. Centoducati; F. Pignatelli; V. Lamargese; A. Salvati; F. Dicuonzo (Case Reports in Ophthalmological Medicine)
Posterior reversible encephalopathy syndrome (PRES) is a neurotoxic state accompanied by a unique brain imaging pattern. This cliniconeuroradiological entity usually presents with visual disturbances (cortical blindness, homonymous hemianopia, visual neglect, and blurred vision) along with neurotoxic manifestations. Only a few cases of PRES have previously been reported in patients with advanced HIV disease. The authors describe a case of posterior reversible encephalopathy syndrome (PRES) in a patient with advanced HIV/TBC infection who developed a neurotoxic state following TB and ART therapy initiation. They present a comprehensive review of the literature and discuss the pathogenetic hypotheses.